Penerapan Model Sosiodrama untuk Meningkatkan Kemampuan Komunikasi pada Pembelajaran IPAS di Madrasah Ibtidaiyah - Fitriyani, Pipih; Kurniawati, Nia; Widowati, Kawuryansih (STIT Fatahillah, 2026)
This study aims to examine the implementation of the sociodrama learning model on students’ communication skills in the Natural and Social Sciences (IPAS) subject for grade IV-B at MIS Al-Misbah. The research employed a pre-experimental method with a one-group pretest-posttest design. The research instrument consisted of a communication skills test administered before (pretest) and after (posttest) the treatment. The learning material used was “Cultural Diversity”, delivered through three learning sessions covering the topics: (1) The Uniqueness of Community Practices, (2) The Richness of Indonesian Culture, and (3) Ways to Preserve Indonesian Culture. The pretest results showed the lowest score of 40, the highest score of 70, and an average of 53.08, categorized as fairly good. After applying the sociodrama model, the posttest results improved, with the lowest score of 70, the highest score of 90, and an average of 79.23, categorized as high. The Shapiro-Wilk normality test indicated that both pretest and posttest data were not normally distributed. Therefore, the Wilcoxon test was conducted and produced a significance value of <.001, which is less than 0.05. This indicates a significant difference between students’ communication skills before and after the treatment, meaning that the communication skills of grade IV students in the IPAS subject improved after using the sociodrama model. This improvement was influenced by the characteristics of the sociodrama model, which actively engages students through role-play, group discussions, and cultural value reflection, thereby enhancing speaking and listening skills as well as building self-confidence. Thus, the sociodrama learning model can serve as an effective alternative learning strategy to improve students’ communication skills in IPAS, particularly in contextual and cultural topics.